Risk, institutions and growth: Why England and not China? - Avner Greif; Murat Iyigun; Diego Sasson (Institute for the Study of Labor (IZA), 2011)
We analyze the role of risk-sharing institutions in transitions to modern economies. Transitions requires individual-level risk-taking in pursuing productivity-enhancing activities including using and developing new knowledge. Individual-level, idiosyncratic risk implies that distinct risk-sharing institutions - even those providing the same level of insurance - can lead to different growth trajectories if they differently motivate risk-taking. Historically, risk sharing institutions were selected based on their cultural and institutional compatibility and not their unforeseen growth implications. We simulate our growth model incorporating England's and China's distinct pre-modern risk-sharing institutions. The model predicts a transition in England and not China even with equal levels of risk sharing. Under the clan-based Chinese institution, the relatively risk-averse elders had more control over technological choices implying lower risk-taking. Focusing on non-market institutions expands on previous growth-theoretic models to highlight that transitions can transpire even in the absence of exogenous productivity shocks or time-dependent state variables. Recognizing the role of non-market institutions in the growth process bridges the view that transitions are due to luck and the view that transitions are inevitable. Transitions transpire when luck creates the conditions under which economic agents find it beneficial to make the choices leading to positive rates of technological change. Luck came in the form of historical processes leading to risk-sharing institutions whose unintended consequences encouraged productivity-enhancing risk-taking.
urn:nbn:de:101:1-201104134225
Keywords: O10; O31; O43; N10; 330; institutions; risk; growth; development; Risiko; Versicherung; Institutioneller Wandel; Wachstumstheorie; Entwicklungstheorie; Theorie; Wirtschaftsgeschichte; Simulation; England; China